Changes in Communication Patterns in the Digital Age - Tika Dewi Amelia, Lolitha; Rania Balqis, Nadira (PT ARRUS Intelektual Indonesia, 2023)
This study discusses changes in communication patterns in the digital era with a focus on the influence of social media on social interaction. The purpose of this study is to describe and analyze how social media has influenced the way humans interact in social contexts. This research was conducted using a qualitative approach through literature studies that collected and analyzed articles, journals, and reliable sources related to changes in communication behavior and social interaction due to the use of social media. The results of the research show that social media has changed traditional communication patterns and formed new ways of social interaction. It found that the use of social media can result in increased global connectivity but also presents challenges related to privacy, changing communication norms, and new forms of nonverbal communication. Keywords: communication change, digital era, social media, social interaction, literature study, media influence.